The United States in the Asia-Pacific since 1945 - Buckley, Roger, 1944- (Cambridge University Press, 2002)
An incisive introduction to America's relationship with the Asia-Pacific region from the end of the Pacific War to the present day it traces the responses of the United States to the major crises in the area.